Implementation of Customer Relationship Management: The Effect of Brand Image on SMES in Siak Regency - Asra, Yunelly; Mubarak, Husni; Maulana, Hutomo Atman; Aulia, Aulia; Syahputri, Melviana (Politeknik Negeri Bengkalis, 2024)
This study aims to determine the effect of brand image on the implementation of customer relationshipmanagement by SMEs in Siak Regency. The population of this study was all the SMEs in Siak Regency and used theslovin formula as a sampling technique. Data collection techniques used surveys, observational and In Deph Interviews.Data analysis technique used simple linear regression. The result of this study show that: The brand image have positiveand significant effect on implementation of customer relationship management with contribution of 75,4%.